Neuropeptide Y Reduces Social Fear in Male Mice: Involvement of Y1 and Y2 Receptors in the Dorsolateral Septum and Central Amygdala - Kornhuber, Johannes; Zoicas, Iulia (International Journal of Molecular Sciences, 2021)
Neuropeptide Y (NPY) has anxiolytic-like effects and facilitates the extinction of cued and contextual fear in rodents. We previously showed that intracerebroventricular administration of NPY reduces the expression of social fear in a mouse model of social fear conditioning (SFC) and localized these effects to the dorsolateral septum (DLS) and central amygdala (CeA). In the present study, we aimed to identify the receptor subtypes that mediate these local effects of NPY. We show that NPY (0.1 nmol/0.2 mu L/side) reduced the expression of SFC-induced social fear in a brain region- and receptor-specific manner in male mice. In the DLS, NPY reduced the expression of social fear by acting on Y2 receptors but not on Y1 receptors. As such, prior administration of the Y2 receptor antagonist BIIE0246 (0.2 nmol/0.2 mu L/side) but not the Y1 receptor antagonist BIBO3304 trifluoroacetate (0.2 nmol/0.2 mu L/side) blocked the effects of NPY in the DLS. In the CeA, however, BIBO3304 trifluoroacetate but not BIIE0246 blocked the effects of NPY, suggesting that NPY reduced the expression of social fear by acting on Y1 receptors but not Y2 receptors within the CeA. This study suggests that at least two distinct receptor subtypes are differentially recruited in the DLS and CeA to mediate the effects of NPY on the expression of social fear.
CRIS-Team WoS Importer:2021-10-08